Mitomycin C in the Endoscopic Treatment of Laryngotracheal Stenosis: Systematic Review and Proportional Meta-Analysis - Queiroga, Thereza L. O. [UNESP] (2020)
Universidade Estadual Paulista, Faculdade de Ciências Médicas e Biológicas de Botucatu